Keragaman Herba Urban Pinggir Jalan Saat El-Niño 2015-2016 di Universitas Indonesia, Depok: Dominasi Spesies Asing - Wendy A. Mustaqim; Aulia S. Ningrum; Windra Suffan (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
One of the focuses of urban ecology is a study that regarded the native versus alien species. During the 2015-2016 El-Niño event, we have conducted an analysis on the diversity of living roadside herbs in a green landscape of Western Java from Universitas Indonesia. The result of the study revealed that a high percentage of non-native species (41.67%) in a roadside ecosystem during the El-Niño event. Axonopus compressus which is an alien species is the most important species based on its importance value index with 74.01%. This condition, together with the high percentage of non-native species show the resistance of those group in its new environment outside their native range even in one of the driest period. It also shows the possibility of such a group to become persist if the habitat of the native species affected by temperature increases, such as climate change.